2013
DOI: 10.3389/fpsyt.2013.00025
|View full text |Cite
|
Sign up to set email alerts
|

Genealogy of instruments for prodrome evaluation of psychosis

Abstract: Objective: Over the last 15 years, researchers from around the world have developed instruments for assessing the risk of conversion to psychosis. The objective of this article is to review the literature on these instruments by focusing on genealogy links and on their performance in predicting conversion to psychosis.Method: A systematic review of articles published since 1980 relating to risk assessment instruments for conversion to psychosis by manual search and consultation of electronic databases MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…Also, lack of longitudinal data did not allow us to assess the factor of later conversion to psychosis, which might be considered in a larger cohort analysis. Different approaches to classifying ultra-high risk subjects will obviously also have an impact on classification of subgroups (on clinical grounds); yet, our use of CAARMS has the advantage of applying one of the best validated instruments in the field (Daneault et al, 2013).…”
Section: Co-ordinates For Maximum Voxelmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, lack of longitudinal data did not allow us to assess the factor of later conversion to psychosis, which might be considered in a larger cohort analysis. Different approaches to classifying ultra-high risk subjects will obviously also have an impact on classification of subgroups (on clinical grounds); yet, our use of CAARMS has the advantage of applying one of the best validated instruments in the field (Daneault et al, 2013).…”
Section: Co-ordinates For Maximum Voxelmentioning
confidence: 99%
“…There are now wellvalidated clinical instruments (Daneault et al, 2013), which have been used to screen young people at high risk for later onset of psychosis, both with the aim of identifying early intervention strategies, as well as enabling biological research into well-defined high-risk populations. Most of these assessments rely on clinical signs and symptoms, including basic symptoms, the occurrence of brief or attenuated psychotic symptoms, psychometric schizotypy, or biological factors such as familial liability (Addington and Heinssen, 2012;Schultze-Lutter et al, 2012;Daneault et al, 2013). Among the most widely used clinical and research instruments, the CAARMS interview (comprehensive assessment of at-risk mental state (Yung et al, 2002)), for example, considers several clinical factors, including higher genetic load (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daneault et al [11] identified 22 instruments with the most widely used measures being clinician administered interviews addressing previously well-validated clinical high-risk criteria [12]. The prognostic accuracy of these thorough psychometric measures is sufficient for help-seeking subjects with psychiatric symptoms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, a number of clinical instruments have been devised to identify individuals who are at risk of developing a psychotic illness. These instruments differ in the extent to which they monitor attenuated psychotic symptoms, basic symptoms, and functional status [3]. The Comprehensive Assessment of At Risk Mental State (CAARMS) is a structured interview designed to identify individuals considered to be at ultra-high risk (UHR) of developing psychosis [4].…”
Section: Introductionmentioning
confidence: 99%